Traditional and mechanized rice farming in Alangalang, Leyte a comparative study. - Cinco, Virgilio L., Jr.; Cular, Anita G. (Virgilio L. Cinco, 2018)
This paper is a comparative study about traditional and mechanized rice farming in 26 randomly selected barangay in Alangalang, Leyte. Specifically, this study compares the level of labor inputs, amount of monetary and explicit costs, level of output and problems associated with traditional and mechanized rice farming. Also, this study determined the significant factors affecting the decision of rice farmers in adopting either traditional or mechanized methods in rice farming. Personal structured interviews were conducted with the 182 randomly selected rice farmers in the research locale. Data collected were analyzed using descriptive statistics, inferential statistics and binary logistic regression. Mechanized rice farming requires lesser labor inputs and lesser monetary and explicit costs compared to traditional rice farming. Yield per hectare of mechanized rice farmers was found to be relatively higher than traditional rice farmers. Problems faced by traditional rice farmers were associated with the attitude and mentality of farm service providers while problems faced by mechanized rice farmers were about machine malfunctions. Regression results show that the significant factors affecting the decision of rice farmers to adopt either traditional or mechanized rice farmers were age, other sources of income and size of land. The researchers recommend that rice farmers should join in farmers' organizations to facilitate exchange of information, ideas and strategies with regards to increasing and improving rice production. Furthermore, policy makers should ensure that policies and programs are inclusive, strictly implemented and properly evaluated.
A research paper (BASS Economics) -- University of the Philippines, Tacloban.